Sistem Kerjasama Usaha Pada Produk Kerajinan Usaha Mikro Kecil Menengah Menurut Konsep Musyarakah (Studi Pada Galeri Menong Purwakarta) - Mia Maulani; Siti Hapipah; Ahmad Saepudin (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2022)
The development of public facilities in the Purwakarta Regency Government continues to be developed in the tourism sector, the results are quite significant in increasing tourist visits. This increase is not only in the tourism sector, but also the superior product of Purwakarta Regency as one of the typical souvenirs of Purwakarta. As a real effort to increase the value of MSME products in Purwakarta, the Menong Gallery was established. This study aims to determine the mechanism of cooperation on the craft of Micro, Small and Medium Enterprises at the Menong Gallery, Purwakarta and to determine the cooperation system for Micro, Small and Medium Enterprises with the concept of Musyarakah at the Menong Gallery, Purwakarta. The research method used in this research is descriptive qualitative method, where data collection is done through observation, interviews, and documentation. The results of this study conclude that the mechanism of cooperation in the craft of Micro, Small and Medium Enterprises at the Menong Gallery, Purwakarta is basically carried out based on the principle of trust. Product custody is based on trust provided that the product has a certification from the Health Service and Halal Certification from the Indonesian Ulema Council. The product also has its own brand and with attractive packaging. This is proven by the completeness of the file and product samples for reference. The cooperation system for micro, small and medium enterprises with the concept of musharaka at the Menong Gallery, Purwakarta is still not in accordance with the concept of a musharaka contract or syirkah. Because there are still many conditions for each pillar that are defective or not fulfilled, such as not meeting the requirements of Ra's Mal, Profit Sharing Ratio, Business Activities, Profits and Losses.